Mugil cephalus Linnaeus 1758 ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Mugil cephalus Linnaeus, 1758. Flathead Mullet, Grey Mullet, or Striped Mullet. To 135 cm (53.1 in) TL (Robertson and Allen 2002). Circumglobal; western Pacific Ocean north to Japan (Senou in Nakabo 2002), Sea of Okhotsk, and southern Kuril Islands (Parin 2003); Humboldt Bay, northern California (Wallace et al. 2015) to Chile and Islas Galápagos (Eschmeyer and Herald 1983). Coastal, marine, brackish, fresh waters (Fricke et al. 2020); depth: in sea, intertidal to 122 m (400 ft) (min.: Robertson and Allen 2002; max.: Eschmeyer and Herald 1983). Mugil cephalus appears to be a species complex (Neves et al. 2020). ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 91, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...